Enfermedad celíaca. Estudio de 36 casos. - Blanco Rabassa, F.; Sagaró González, E.; Fragoso Arbelo, T.; Castañera Guillot, C.; Valenti, J. (Revista Cubana de Pediatría, 2023)
Presenta el resultado del trabajo de dos años.